2020
DOI: 10.1186/s13071-020-04038-w
|View full text |Cite
|
Sign up to set email alerts
|

Angiostrongylus cantonensis Galectin-1 interacts with Annexin A2 to impair the viability of macrophages via activating JNK pathway

Abstract: Background: Angiostrongylus cantonensis can cause severe symptoms of central nervous system infections. In the host, this parasite localizes in the blood and cerebrospinal fluid, and its secreted components can impact immune responses. Our previous study demonstrated that immune responses were inhibited in A. cantonensis-infected mice immunized with Ac-Galectin-1 (AcGal-1). However, the mechanisms by which AcGal-1 regulates the immune responses remain unclear. Macrophages are innate immune cells that rapidly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…In mice, vaccination against Angiostrongylus cantonensis galectin inhibits the immune response to subsequent infection with A. cantonensis (Yan et al ., 2018). Angiostrongylus cantonensis gal-1 causes apoptosis of macrophages by binding to Annexin A2 and activating the apoptotic signalling pathway (Shi et al ., 2020).…”
Section: Interactions Between Host and Nematode Galectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, vaccination against Angiostrongylus cantonensis galectin inhibits the immune response to subsequent infection with A. cantonensis (Yan et al ., 2018). Angiostrongylus cantonensis gal-1 causes apoptosis of macrophages by binding to Annexin A2 and activating the apoptotic signalling pathway (Shi et al ., 2020).…”
Section: Interactions Between Host and Nematode Galectinsmentioning
confidence: 99%
“…In mice, vaccination against Angiostrongylus cantonensis galectin inhibits the immune response to subsequent infection with A. cantonensis (Yan et al, 2018). Angiostrongylus cantonensis gal-1 causes apoptosis of macrophages by binding to Annexin A2 and activating the apoptotic signalling pathway (Shi et al, 2020). The changes in mucus following infection are at least partly host-mediated and widely assumed to benefit the host (Knight et al, 2011;Hasnain et al, 2017).…”
mentioning
confidence: 99%
“…Galectins are secreted by cells via an unconventional mechanism [ 21 , 22 ] and function in various biological phenomena, such as development, immunity and tumorigenesis via recognition of cell surface or extracellular glycoconjugates [ 22 ]. Parasite galectins have a sequence and structure similar to those of mammalian homologs and are presumed to participate in host-parasite interactions [ 23 , 24 ]. Our previous studies showed that upregulated Acan -Gal-1 in A. cantonensis L5 induced the apoptosis of macrophages by binding to Annexin A2 and activating the JNK apoptotic signaling pathway [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Galetins are secreted by cells via an unconventional mechanism [21,22], and function in various biological phenomena, such as development, immunity and tumourigenesis via recognition of cell surface or extracellular glycoconjugates [22]. Parasite Galetins have a sequence and structure similar to those of mammalian homologs and are presumed to participate in host-parasite interactions [23,24].Our previous studies showed that up-regulated Acan-Gal-1 in A. cantonensis L5 induced the apoptosis of macrophages by binding to Annexin A2 and activating the JNK apoptotic signaling pathway [24]. However, galectins are also found intracellularly, and are involved in RNA splicing, cell growth, apoptosis and other functions [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As LEC-1 is mainly localized in the cuticle and pharynx of C. elegans [32], it is thought to have some functions as a component of the durable outer barrier via recognizing and cross-linking glycoconjugates by its two CRDs with different sugar-binding properties, and play a defensive role against damage due to oxidative stress in C. elegans [33]. Therefore, Acan-Gal-1, up-regulated in A. cantonensis L5, may have function of resisting immune attacks in human by not only inducing the apoptosis of its host's macrophages extracellularly [24], but also increasing oxidative stress tolerance of the worm itself intracellularly.…”
Section: Introductionmentioning
confidence: 99%